Analysis of the Behaviour of the Hydraulic Fluid HM VG 32 and HV 32 at Different Operating Conditions of the Axial-Piston Pump - Borivoj Novaković; Ljiljana Radovanović; Mića Đurđev; Luka Đorđević; Eleonora Desnica (Tehnički Vjesnik, 2024)
This paper investigates the behaviour of two types of hydraulic fluids, ISO HM VG 32 and ISO HV VG 32, in hydraulic presses under various operating conditions. The study aims to analyze the influence of these fluids on hydraulic system performance and testing, considering factors such as viscosity, density, and the presence of solid particles. The authors address the problem of hydraulic press systems driven by an axial-piston pump and the changes that occur in different types of fluids of the same kinematic viscosity but of different viscosity grades. Experimental research compares the performance of HM and HV oils before and after filtration, examining parameters such as viscosity and density under different pressures and temperatures. Results indicate that HV oils perform better under high-temperature conditions, while HM oils demonstrate superior performance under normal operating conditions. The study emphasizes the importance of continual monitoring and maintenance to optimize hydraulic system performance and mitigate potential risks associated with fluid contamination.